Identification of an epigenetic biomarker predicting the response to therapy with APG101 in glioblastoma - Thiemann, Markus; Wiestler, Benedikt; Wick, Wolfgang (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: APG101, a fully human fusion protein consisting of the extracellular domain of CD95 and the Fc-domain of an IgG, has been developed by Apogenix. It was confirmed as a potent inhibitor of CD95L induced invasion of glioblastoma cells in vitro. In a randomized phase 2 study in glioblastoma patients with 1st or 2nd relapse the combined therapy of APG101 plus radiotherapy (RT) was found to be superior to RT alone in a clinically relevant order of magnitude in all efficacy endpoints (i.e. PFS-6, PFS and OS). At the same time APG101 exhibited an excellent safety profile and was well tolerated. The presented data summarizes the identification of a predictive biomarker.Methods: To identify potential biomarkers we used available tissue sections originating...